Spatial Planning and Urban Open Space Utilization in Banda Aceh: A Policy Implementation Review - Aditya, Atika; Irwansyah, Mirza (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study examines the implementation of regional spatial planning (RTRW) policy in the utilization of public open spaces in Banda Aceh’s city center. Public open spaces play a critical role in urban environments, providing ecological, social, and recreational benefits. However, the success of spatial planning policies depends heavily on their realization on the ground. This research employs a qualitative approach, combining field observations with document analysis to assess whether the public open space components outlined in Banda Aceh’s RTRW are being implemented. The findings reveal a notable discrepancy between planning and execution. Several public areas that have been designated as open spaces in the RTRW remain undeveloped or neglected, with limited government intervention or infrastructure development. This disconnect suggests issues in policy enforcement, budgeting, or coordination among relevant stakeholders. As a result, the potential of these spaces to contribute to urban sustainability and community well-being remains underutilized. The study underscores the need for more consistent monitoring, cross-sector collaboration, and community involvement to ensure that spatial planning policies are effectively translated into functional and accessible public open spaces. Strengthening the implementation process could play a significant role in enhancing the urban quality of life in Banda Aceh.